Meningkatkan Pemahaman Siswa Tingkat Sekolah Dasar dalam Pembelajaran Matematika di Masa Pandemi Covid-19 - Safitri, Fadlia Laili; Janah, Nadila Miftahul; Nandus, Viorentiary Ferry; Aliah, Hasniah; Paryati, Paryati (PROCEEDINGS UIN SUNAN GUNUNG DJATI BANDUNG, 2022)
Pembelajaran Jarak Jauh Policy (PJJ) in the midst of the Covid-19 pandemic is burdensome for some people who have school-age children. Parents' lack of understanding of the subjects taught at school, especially Mathematics and online learning methods of Mathematics is also a major problem faced by parents. Therefore, the community really needs a learning assistance program for students. The service program is carried out by students in the Real Work From Home Lecture scheme with the Community Empowerment System (KKN-DR Sisdamas) method. This program is in the form of assistance in learning Mathematics for elementary school students in Kp. Kebayunan, Depok City, which was held for approximately three weeks. During the learning process, it was seen that students' enthusiasm was very large for this learning mentoring program. This causes students' understanding of mathematics to increase significantly, as indicated by a change in students' understanding of the basic concepts of mathematics that were not previously known. Thus, the three points possessed by the Tridharma of higher education can be carried out properly and are useful in the implementation of the 2021 Sisdamas KKN-DR in Depok City.